2011
DOI: 10.1111/j.1745-7599.2011.00598.x
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of foot care services among homeless adults: Implications for advanced practice nurses

Abstract: To increase use of foot care programs among homeless adults, services must be offered during the day time when they are not competing to secure nightly shelter. Foot care programs should be innovative and tailored to their unique needs and address concern for sensitivity to feet, sock, and shoe condition; cost; specific services provided; competing needs; source of care; and how to access these services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 16 publications
(24 reference statements)
0
31
0
Order By: Relevance
“…[11], [12], [16], [17], [19], [20], [23], [24] One study recruited homeless individuals from a volunteer health service outreach association, [25] and another study recruited homeless individuals from a community kitchen. [18] Ten (59%) studies included participants from more than one location (e.g. shelters, clinics).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[11], [12], [16], [17], [19], [20], [23], [24] One study recruited homeless individuals from a volunteer health service outreach association, [25] and another study recruited homeless individuals from a community kitchen. [18] Ten (59%) studies included participants from more than one location (e.g. shelters, clinics).…”
Section: Resultsmentioning
confidence: 99%
“…[13] In one study of homeless adults who used foot care services, 56% reported a history of diabetes, hypertension, peripheral vascular disease or a combination of the three. [18] In one study of 299 homeless shelter residents, approximately 9% self-reported having diabetes with 5% having diabetes mellitus type 2 and 4% having diabetes mellitus type 1. [19] However, 16% of participants reported numbness, 21% had tingling in their feet, and 21% had swollen feet suggesting that some individuals may have had undiagnosed diabetes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations